2011
DOI: 10.1097/meg.0b013e3283496502
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of standard-dose versus half-dose rabeprazole, clarithromycin, and amoxicillin in the treatment of Helicobacter pylori infection

Abstract: A half-dose 10-day regimen of rabeprazole, amoxicillin, and clarithromycin is equally effective but cheaper and better tolerated than its standard-dose regimen in the treatment of Helicobacter pylori. Eradication rates of both regimens are, however, suboptimal compared with accepted standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…Increasing efficacy by prolongation of therapy was also noted in Greek patients, with eradication rates of 74.5% for 7 days, 80.6% for 10 days, and 90.2% for 14 days of therapy [4]. Another study showed that efficacy could be maintained when lower doses of medications were given, which reduced costs and side effects with cure rates of 77.2% for 10 mg rabeprazole, 500 mg amoxicillin, and 250 mg clarithromycin vs 78.9% for the standard 20 mg, 1 g, and 500 mg doses of these drugs [5].…”
Section: Triple Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing efficacy by prolongation of therapy was also noted in Greek patients, with eradication rates of 74.5% for 7 days, 80.6% for 10 days, and 90.2% for 14 days of therapy [4]. Another study showed that efficacy could be maintained when lower doses of medications were given, which reduced costs and side effects with cure rates of 77.2% for 10 mg rabeprazole, 500 mg amoxicillin, and 250 mg clarithromycin vs 78.9% for the standard 20 mg, 1 g, and 500 mg doses of these drugs [5].…”
Section: Triple Therapymentioning
confidence: 99%
“…Increasing efficacy by prolongation of therapy was also noted in Greek patients, with eradication rates of 74.5% for 7 days, 80.6% for 10 days, and 90.2% for 14 days of therapy [4]. Another study showed that efficacy could be maintained when lower doses of medications were given, which reduced costs and side effects with cure rates of 77.2% for 10 mg rabeprazole, 500 mg amoxicillin, and 250 mg clarithromycin vs 78.9% for the standard 20 mg, 1 g, and 500 mg doses of these drugs [5].Regardless of the type of therapy used, study from Canada showed widespread failure to comply with test and treat in up to 10% of cases and a failure to confirm eradication in 32% [6]. This illustrates that efficacious first-line therapy will always depend on adherence to guidelines by physicians and compliance with therapy by patients.…”
mentioning
confidence: 99%
“…To date, three randomized controlled trials, involving a total of 475 patients, have examined the value of 50% reduction in the dose of all administered antibiotics for H. pylori (two STT and the current concomitant NBQT) and have all confirmed similar eradication rates to the standard-dose comparator (Table 4), with a reduction in adverse events and cost. 13,33 This concept is attractive and challenges the prevailing dogma in the treatment of H. pylori. One theoretical concern, however, is that these low-dose regimens may produce prolonged sub-minimum inhibitory concentration effects which may, in turn, contribute to development of resistant strains.…”
Section: Discussionmentioning
confidence: 99%
“…The overall eradication rate was, however, suboptimal (77.6% with standard-dose therapy and 77.2% with half-dose triple therapy on ITT), signalling a 13.8% decline in eradication rate of the exact standard-dose regimen over a 6-year period within the same geographic area and institution. 13,14 Based on the reported superiority of NBQT and the promising concept of reduced-dose combination therapy, this study was designed to investigate the efficacy and safety of 7-day standard-dose vs. half-dose concomitant NBQT regimen for the eradication of H. pylori infection.…”
Section: Introductionmentioning
confidence: 99%
“…elicobacter pylori is a significant cause of chronic active gastritis, peptic ulcer disease, and gastric cancer (1). Several strategies have been proposed for eradication of H. pylori, including the standard first-line treatment (standard triple therapy [STT]) and quadruple, sequential, and concomitant treatments (2).…”
mentioning
confidence: 99%